3a-b=11

Simple and best practice solution for 3a-b=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3a-b=11 equation:


Simplifying
3a + -1b = 11

Solving
3a + -1b = 11

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add 'b' to each side of the equation.
3a + -1b + b = 11 + b

Combine like terms: -1b + b = 0
3a + 0 = 11 + b
3a = 11 + b

Divide each side by '3'.
a = 3.666666667 + 0.3333333333b

Simplifying
a = 3.666666667 + 0.3333333333b

See similar equations:

| 16.85=3.95+3c | | 5-3(x+4)=6 | | 4f+2=8 | | 8+(7x-6)=3 | | 6(y+7)+y=3(y+2)-8 | | 7x-8y=13findy | | 3x+9y=-24 | | 2ab-7b-5ab-6b= | | 7x-8y=13 | | 3x+4+5x-6=180 | | 8-3(x+2)=7 | | 2(x-7)+4=8 | | 6=6+n | | 2+4x=5x-1 | | 15+(3x-6)=(9+x)2 | | -6.5=-4.3-n | | 5x+1-5x=8 | | x/(-6)=-14 | | x^2-28X+180=y | | (x/4)+3x/2=3/8 | | 8x-19=19+11x | | -6x+2y=-5 | | x/4+3x/2=3/8 | | -5y+21=36 | | 5(5x-2)+3=-1 | | 5x-1x=15-x | | 7(x-6)+28=-21 | | 4x+(4-4x)=4 | | x/21=-3 | | -144=-6k | | 6(6-5)+36-7= | | -1x+8=-7x+2 |

Equations solver categories